An efficient method for detection of key objects in video shots with camera motions - Hwan Oh, Jung; Kyu Lee, Jeong; Hwang, Sae (Revista Colombiana de Computación, 2003)
The most fundamental task in video processing is to partition long video sequences into a number of shots and find a key frame of each shot for indexing and browsing. keywords: Video object segmentacion, shot boundary detection, color quantization, MPEG-4/MPEG-7.